Traction electric drive based on fuel cell batteries and on-board inertial energy storage for multi unit train - V. I. Omelyanenko (National Technical University "Kharkiv Polytechnic Institute", 2021)
The aim of the work is to study the possibility and features of the use of inertial storage devices in the traction electric drive of multi unit train with a power plant based on fuel cells. Methodology. The principle of power flow control in traction electric drives in the modes of acceleration and braking of rolling stock is proposed. The mathematical model of the traction electric drive in the form of the combination of three components: the train, the traction unit and the battery of fuel cells is developed. It was used to study the operation of a traction electric drive when solving a test traction task for rolling stock. Results. It is established that the use of inertial energy storage reduces hydrogen consumption by at least 25 %, which increases the mileage of rolling stock between equipment by more than 30 %. Originality. The traction electric drive on the basis of fuel elements and the inertial energy storage for the multi unit train is offered. The work of the proposed traction electric drive in solving the test traction problem for rolling stock is investigated. Practical significance. A mathematical model of the traction electric drive has been developed. The test traction problem for rolling stock is solved.